The Effect Of Wall-Rebound Training On Underhand Passing Skills In Volleyball Among Students Participating In The Volleyball Extracurri-Cular Activity At Sma Negeri 10 Bandar Lampung - Nanda Meysurah; Joan Siswoyo; Muhammad Fajril Rifaldo; Suwarli (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aimed to determine the effect of wall-rebound training on underhand passing skills in volleyball among students participating in the volleyball extracurricular activity at SMA Negeri 10 Bandar Lampung. The research employed an experimental method with a pre-test and post-test design. The sample was divided into an experimental group that received wall-rebound training and a control group that received conventional training. The research instrument was an underhand passing skill test in volleyball. Data were analyzed using the normality test, homogeneity test, and t-test with a significance level of 0.05. The results showed that the data were normally distributed and homogeneous. The first hypothesis test indicated a significant effect of wall- rebound training on underhand passing skills in the experimental group, with t- value = 19,379 > t-table = 2.145 and Sig. = 0.000 < 0.05. The second hypothesis test revealed a significant difference in underhand passing skills between the experimental group and the control group. Furthermore, the third hypothesis test showed a significant difference in the improvement of underhand passing skills between the experimental group and the control group, with t-value = 2.107 > t- table = 2.048 and Sig. = 0.044 < 0.05. It can be concluded that wall-rebound training is effective in improving underhand passing skills in volleyball among students participating in the volleyball extracurricular activity at SMA Negeri 10 Bandar Lampung